Kolaborasi Antar Stakeholder Dalam Pengembangan Pariwisata Pada Desa Wisata Kandri Kota Semarang - Choirul Ramadhan; Ari Subowo; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Kandri Tourism Village has been running as one of the tourist attractions for approximately 10 years since it officially became a Tourism Village on December 21, 2012. However, in its journey, it experienced a number of obstacles, namely evidenced by the weak pattern of facilitative leadership carried out by stakeholders, resulting in a lack of trust from the people of Kandri Village in the importance of tourism development and the process of submitting the Tourism Development Fee Budget went uneventfully. In addition, the existing tourism supporting infrastructure in this village is still found to be inadequate and abandoned due to the lack of maintenance and supervision from the Village Government and local Tourism Village managers. Based on these problems, researchers are interested in conducting research on facilitative leadership patterns in the collaboration process that have an effect in the development of tourism in Kandri Tourism Village. The purpose of this study is to describe and analyze facilitative leadership patterns in tourism development collaboration in Kandri Tourism Village. The method used in this study is descriptive qualitative. The main research subjects are the stakeholders involved, including: Employees of the Institutional Office of the Semarang City Disbudpar, Kandri Village Government, CSR (PD. BPR BKK) Semarang City and The Kandri Tourism Village Pokdarwis Team with purposive sampling technique. The research site is located in Kandri Tourism Village with data collection techniques through Observation, Interviews and Documentation. The results of the study revealed that the collaboration process that has been carried out so far has experienced several obstacles as evidenced by the analysis of Ansell and Gash's collaborative governance model such as how to build relationships, cooperation dialogue models, meetings and commitments carried out as well as the Division of Roles and Responsibilities.